The double value of the typological analysis in the protection of the Ensanche de Valencia - Alonso De Armiño Pérez, Luis Carlos (2022)
This paper discusses two typological studies, carried out consecutively, on the buildings composing the historic "Ensanche" of Valencia. The interest of both analyses lies on the different approaches that guides each one. The first analysis, carried out on the occasion of drafting the Ensanche Special Protection Plans (PEP), was aimed at determining the capabilities and limits of the different historic buildings, in view to allow a desirable and necessary update of their use value while, at the same time, ensure the preservation of their identity in terms of perceived form. For its part, the second, in-depth analysis focused on the study of the historical evolution ofthe building-types and the modalities of property business and architectural design over more than half a century. Each of the analysis followed its own methodology, as recorded in the text. The presentation of relevant aspects of both studies intends to offer a perspective on the hypothesis of the double character offered by the typological analysis: on one hand, as a proactive, project-oriented tool, aimed at normative action in heritage preservation and use-value updating, controlling transformation through redesign. On the other hand, the analysis as a scientifically based research tool for interpreting the historical evolution of urban fabric. Both have proved complementary, and useful for discussing heritage twofold meaning: formal control and cultural perception.